2019
DOI: 10.1016/j.molmed.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Hurdles for Tissue-Engineering the Temporomandibular Joint Disc

Abstract: Current treatments for TMDs lack long-term efficacy and are palliative, motivating tissue-engineering for repair or replacement of the injured or ailing tissues in the TMJ, such as the disc. Scaffold-based or scaffold-free approaches, cell sources, biochemical stimuli, and mechanical stimuli are all elements of the tissue-engineering process that need to be considered to tailor TMJ disc construct properties. Large animals can serve as models of human TMDs orthotopic implantation in large animal models is a nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…Previous studies have suggested that passaged costal chondrocytes outperform TMJ disc cells in TMJ disc engineering and concluded that passaged costal chondrocytes appear to be the most promising cell source for scaffold‐free tissue engineering of the TMJ disc (Anderson & Athanasiou, 2008; Donahue, Hu, & Athanasiou, 2019). Therefore, costal chondrocytes were selected in this study to evaluate the cellular compatibility of the hydrogel in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that passaged costal chondrocytes outperform TMJ disc cells in TMJ disc engineering and concluded that passaged costal chondrocytes appear to be the most promising cell source for scaffold‐free tissue engineering of the TMJ disc (Anderson & Athanasiou, 2008; Donahue, Hu, & Athanasiou, 2019). Therefore, costal chondrocytes were selected in this study to evaluate the cellular compatibility of the hydrogel in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic side effects from oral drugs, such as gastrointestinal damage, cardiovascular risk, and anaphylaxis, and those from frequent intra-TMJ injections, including dizziness, dry mouth, and possible drug addiction, are raising concern. Meanwhile, conventional palliative drug treatments show limitation in the regeneration of chronic and severe TMD (Dashnyam et al, 2018;Donahue et al, 2019). Therefore, novel IA systems, several of which show potential in animal TMD model, that contain biomaterials, cells, and/or bioactive molecules for sustained drug release and TMJ tissue regeneration are attracting attention (Table 3).…”
Section: Novel Intra-articular Bioactive Agent Delivery Systems For Treating Tmdmentioning
confidence: 99%
“…For the severe types of TMD, such as internal derangement, disc thinning, disc perforation, and osteochondral damage of condyle, regenerative tissue engineering approaches are in demand. Such systems typically consist of bioactive agents, including scaffold, cells, and/or GFs (Donahue et al, 2019;Aryaei et al, 2016;Acri et al, 2019).…”
Section: Novel Delivery Systems For Regenerative Agentsmentioning
confidence: 99%
See 2 more Smart Citations